Exploring the correlation between Drp1 protein and the neurotoxicity of propofol - Pu Guo; Jing Mei (Frontiers in Neuroscience)
Neurotoxicity is a common toxic reaction associated with the use of the anesthetic drug propofol. With the widespread use of propofol, the issue of neurotoxicity has garnered significant attention. Mitochondria are the energy metabolism centers of cells and play a crucial role in biological processes such as cell growth and development, invasion and metastasis, division and differentiation, and apoptosis. Dynamin-related protein 1 (Drp1) is a key regulator of mitochondrial fission that can modulate the dynamic balance of mitochondria and plays an important role in maintaining mitochondrial morphology and function. The abnormal expression of Drp1 is closely related to the occurrence and development of various pathological conditions. Through a systematic review of multi-species animal and cellular studies, we elucidated the correlation between Drp1 and propofol-induced neurotoxicity. By analyzing Drp1-mediated mitochondrial fragmentation across different organ systems, this work provides crucial theoretical foundations for developing Drp1-targeted strategies in propofol neurotoxicity detection, prevention, and pharmacological intervention.